Central Bank Independence and Inflation in the MENA Region: Does Institutional Quality Matter? - Mouatassim, Abdellatif; Kchikeche, Ahmed; El Hiri, Abderrazak; Echaoui, Abdellah (Ekonomika, 2025)
This paper examines the impact of Central Bank independence on Inflation in 16 MENA countries from 1990 to 2017. By employing a two-stage least squares instrumental variables approach, the study assesses the influence of three legal independence measures on the inflation rate. It investigates the moderating role of institutional quality in the relationship between these two variables. The findings robustly demonstrate that an increased Central Bank independence leads to lower inflation rates across all measures, model specifications, and estimation methods. Moreover, institutional quality not only directly reduces inflation but also enhances the negative impact of the Central Bank independence on inflation. Consequently, the study suggests that policymakers in MENA countries should reinforce the independence of monetary authorities and improve the overall institutional quality to maintain price stability.
Keywords: Central Bank Independence; Inflation; Institutional Quality; MENA; Two-Stage-Least-Squares